The Application of Mini Seminar at MAN 2 Kota Makassar - M. David Hidayatulloh; Samtidar Samtidar; La Sunra (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
Anxiety is the most common factor that attacks EFL students in mastering that language. This study aims to explore the use of mini-seminar in coping with students’ anxiety. The researcher applied a descriptive qualitative research model to acquire the objective of the research. The data of this research were collected by the implementation of non-participant observation and student interviews. The subject of the research was five EFL students in the English Club of MAN 2 Kota Makassar (Islamic English Teenagers), which formed from students in grade tenth to eleventh. Furthermore, the result of the research found that this mini seminar has several advantages as this mini seminar could help the students to build their experiences, build their confidence, improve their public speaking skills, and help them to perform well. In addition, the students’ argumentation indicated that these mini seminar’s advantages could help them to overcome their anxiety.